Quality planning, control and improvement in research and development - Roberts, George W (Quality and reliability, 1995)
This work provides the tools required to help researchers reduce risks and minimize costs, emphasizing the techniques that achieve and improve quality, as well as illustrating the need for change in current laboratory management practices. The book features an in-depth study of the strengths and weaknesses of peer review, with checklist examples from the US office of naval research.;The book is intended for quality, reliability, industrial, design, process, manufacturing, chemical, mechanical, metallurgic and electrical and electronics engineers; cost analysts; physicists; chemists; chief executive officers; laboratory managers and administrators; and upper-level undergraduate and graduate students in these disciplines.